Influence of respiratory biofeedback associated to re-expansive ventilation patterns in individuals with functional mouth breathing - Barbiero, Eliane de Faveri F.; Marques Vanderlei, Luiz Carlos [UNESP]; Scalabrini Neto, Augusto; Nascimento, Patricia C. (Elsevier B.V., 2008)
Objectives: Assess the effect of re-expansive respiratory patterns associated to respiratory biofeedback (RBF) on pulmonary function, respiratory muscle strength and habits in individuals with functional mouth breathing (FMB).Methods: Sixty children with FMB were divided into experimental and control groups. The experimental group was submitted to 15 sessions of re-expansive respiratory patterns associated to RBF (biofeedback pletsmovent; MICROHARD (R) V1.0), which provided biofeedback of the thoracic and abdominal movements. The control group was submitted to 15 sessions using biofeedback alone. Spirometry, maximum static respiratory pressure measurements and questions regarding habits (answered by parents/guardians) were carried out before and after therapy. The Student's t-test for paired data and non-parametric tests were employed for statistical analysis at a 5% Level of significance.Results: Significant changes were found in forced vital. capacity, Tiffeneau index scores, maximum expiratory pressure, maximum inspiratory pressure and habits assessed in FMB with the use of RBF associated to the re-expansive patterns. No significant differences were found comparing the experimental and control groups.Conclusions: The results allow the conclusion that RBF associated to re-expansive patterns improves forced vital capacity, Tiffeneau index scores, respiratory muscle strength and habits in FMB and can therefore be used as a form of therapy for such individuals. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Mouth breathing; Physiotherapy; Respiration